If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 2x = 3y Solving 13 + 2x = 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 2x = -13 + 3y Combine like terms: 13 + -13 = 0 0 + 2x = -13 + 3y 2x = -13 + 3y Divide each side by '2'. x = -6.5 + 1.5y Simplifying x = -6.5 + 1.5y
| 3+2m=27-6m | | 4-3(3x+2)=2x-1 | | x^2=1331 | | 8+5y=7y-12 | | 6(x+6)=6(x+10) | | 6x-6=36x-6 | | m+35+m=155 | | 9y-4=6y+23 | | 35+2m=6m-1 | | -(3x-4y+z)= | | 4x(x-6)-5x(x-5)=-2 | | -1(4x-13)=2(3-2x) | | -(4x-13)=2(3-2x) | | 11-2y+4=8+5x | | .40r-5=7 | | factor=216x^3+27 | | (3k-5)-7k=25 | | 24-3y=2y-1 | | X^(5/3)-7x^(4/3)-8x= | | 3y+2=-4y-12 | | -1=.5a+9 | | n/7=9/4 | | a/9=a-4/5 | | 0.10(x+80)+0.90x=33 | | -[-10x-4]=4x+14 | | 10x-43-8x=13 | | http://media.apexlearning.com/Images/201305/30/4690173e-3b40-45a8-b981-16fc638a0743.gif | | 3m+35=8m+15 | | 15/7 | | 167+19t+16t=1132 | | -2x+16=30+3x | | 8y-6=2y+24 |